ESTERS OF DIPHENYLPHOSPHINOSELENOTHIOIC AND DIPHENYLPHOSPHINODISELENOIC ACIDS WITH POTENTIAL FOR RAFT POLYMERIZATION - CHIOREAN, Nora; POP, Alexandra; SILVESTRU, Cristian; SILVESTRU, Anca (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Compounds of type Ph2P(E)SeR [E = S, R = 2-MeC6H4 (1), 2-(Me2NCH2)C6H4 (2); E = Se, R = 2-(Me2NCH2)C6H4 (3)], were prepared and structurally characterized in solution by multinuclear NMR (1H, 31P, 77Se). The attempts to obtain the derivative Ph2P(S)SeC6H4(CH2NMePri)-2 (4) resulted in a complex mixture. The attempts to separate the components resulted in further decomposition and hydrolysis and the isolated crystals were investigated by single-crystal X-ray diffraction when proved to be the ammonium salt [MePriBnNH]+[Ph2P(S)O]ˉ (Bn = benzyl) (4a).